White matter alterations in neurodegenerative and vascular dementia - Supprian, T; Kessler, H; Retz, W; Rösler, M; Grunwald, I; Reith, W; Falkai, P (2003)
Due to a significant overlap of the two syndromes, differentiation of degenerative dementia of the Alzheimer-type from vascular dementia may be difficult even when imaging studies are available. White matter changes occur in many patients suffering from Alzheimer's disease. Little is known about the impact of white matter changes on the course and clinical presentation of Alzheimer's disease. High sensitivity of MRI in the detection of white matter alterations may account for over-diagnosing vascular dementia. The clinical significance of white matter alterations in dementia is still a matter of debate. The article reviews current concepts about the role of white matter alterations in dementia.